Learning Daily Colloquial Vocabulary English of a Digital Movie - Dhalfa Michele Hermawan; Iskhak Iskhak; Bambang Ruby Sugiarto (Universitas Galuh, 2025)
This research explores the adequacy of utilizing computerized motion pictures to instruct day-to-day colloquial English lexicon to junior high school students. It addresses the constrained lexicon and elocution challenges confronted by Indonesian students learning English. The think about analyzes how computerized motion pictures can improve students' vocabulary acquisition and talking abilities, making the learning handle more locks in and successful compared to conventional strategies. This is a qualitative paradigm with the type of case study involving 20 students and one teacher as research participants. Data collection was gathered from student interviews to assemble information on their learning experiences and challenges. The discoveries recommend that computerized motion pictures, with English subtitles, altogether help in vocabulary learning by providing context and pronunciation cues, subsequently improving comprehension and speaking confidence. In any case, a few downsides include innovation availability issues and potential diversions. The inquiry about underscores the potential of computerized motion pictures as a profitable instrument in dialect instruction, advertising viable experiences for teachers, pointing to coordinated mixed media assets into their educating methodologies to improve language learning results.